1996
DOI: 10.1002/(sici)1096-9861(19960902)372:4<618::aid-cne9>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of crayfish phasic and tonic neuromuscular terminals

Abstract: We examined the fine structure of terminals of the phasic and tonic excitatory axon to the crayfish limb extensor muscle. The phasic terminals are known to release 50-100 times more transmitter for a small length of terminal for a single impulse. Phasic terminals labeled with horseradish peroxidase (HRP) were relatively thin and contained a single unbranched mitochondrion; tonic terminals were much thicker, and their varicosities contained several multibranched mitochondria. Tonic terminals devoted a larger pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 27 publications
8
61
0
Order By: Relevance
“…Terminals of slow and fast neurons innervating crustacean muscles differ in morphological and physiological parameters such as number of release sites, quantal content, and facilitation or depression of transmitter release (Hoyle and Wiersma, 1958;Bittner, 1968;Rathmayer and Hammelsbeck, 1985;Atwood and Wojtowicz, 1986;King et al, 1996;Bradacs et al, 1997;Nguyen et al, 1997;Lnenicka et al, 1998;Msghina et al, 1998Msghina et al, , 1999. While studying peptidergic modulation of release by the FMRFamide-like DF 2 (DRNFLRFamide) and proctolin, we noted that DF 2 affected the slow and fast axons differentially.…”
Section: Abstract: P/q-type Ca 2ϩ Channels; N-type Ca 2ϩ Channels; Rmentioning
confidence: 99%
“…Terminals of slow and fast neurons innervating crustacean muscles differ in morphological and physiological parameters such as number of release sites, quantal content, and facilitation or depression of transmitter release (Hoyle and Wiersma, 1958;Bittner, 1968;Rathmayer and Hammelsbeck, 1985;Atwood and Wojtowicz, 1986;King et al, 1996;Bradacs et al, 1997;Nguyen et al, 1997;Lnenicka et al, 1998;Msghina et al, 1998Msghina et al, , 1999. While studying peptidergic modulation of release by the FMRFamide-like DF 2 (DRNFLRFamide) and proctolin, we noted that DF 2 affected the slow and fast axons differentially.…”
Section: Abstract: P/q-type Ca 2ϩ Channels; N-type Ca 2ϩ Channels; Rmentioning
confidence: 99%
“…Although the varicosities of tonic terminals are much larger, they have a significantly lower transmitter output than phasic terminals at low frequencies of nerve impulse activity (Bradacs et al, 1997;King et al, 1996;Msghina et al, 1998). The two excitatory motor neurons are morphologically different.…”
Section: Introductionmentioning
confidence: 48%
“…In fact, it was shown that phasic terminals, in the same type of NMJ preparations as used in our study, have a 2Á/3 times larger amount of calcium entering during evoked stimulation as compared to tonic terminals . This difference appears to be related to the differences in the calcium channels of the two terminals as well as synaptic structure in the degree of spacing between active zones on synapses (King et al, 1996;Cooper et al, 1996b;Msghina et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations